Enhancing Entrepreneurship in Pesantren Through the Synergy of Islamic Education and Sharia Based Human Resource Management - Fakhry Hafiyyan Kurniawan; Edi Suryadi; A. Sobandi; Eeng Ahman; Heriman Heriman; Mahbub Afini Maulana; Mohammed Abyannash (SYAMIL: Journal of Islamic Education, 2025)
Entrepreneurship education is a process of creating a product that has uniqueness or benefits by optimizing the resources used. Nowadays, the implementation of entrepreneurial values has been carried out by pesantren, which not only focuses on the social and educational pillars. On one hand, as an effort for pesantren individuals to continuously adapt to the challenges of the times related to education and entrepreneurship, optimal utilization and application of Islamic Human Resource Management (HRM) is required. Currently, pesantren face challenges such as the lack of integration between educational and entrepreneurial curricula, the suboptimal role of pesantren leadership, and the limited use of appropriate technology. This research aims to examine strategies to enhance the role of entrepreneurship education in pesantren. The study employs a qualitative approach, collecting data through interviews with 12 pesantren leaders and direct observations at pesantren in the Sukabumi and Cianjur regions. The data analysis technique used is the SWOT Matrix, analyzed thematically to develop appropriate strategic patterns. The results indicate that with the right strategy, pesantren can become a role model in the development of Islamic economic and financial sectors as well as the implementation of Islamic HRM. This aligns with the goals of education, which are to shape individuals who are not only intelligent but also independent, productive, and possess social and spiritual sensitivity, ultimately supporting the economic independence of pesantren and contributing to society